How to Depict Memory? The Holocaust in Polish Illustrated Children’s Books - Kwiatkowska, Agnieszka (Porównania, 2021)
The focus of this article is an analysis of illustrations in several children’s books that refer to the topic of the Holocaust. The majority of the studied pictures are realistic in their style, some resemble children’s drawings or use photographs. Such a manner of illustrating books serves the purpose of authenticating a story. The most important motifs repeated in numerous illustrations are: seeking a hideout, the experience of hunger and fear of loosing one’s mother. The illustrations do not, however, image drastic situations. They rather aim at commemorating the Holocaust, they render a collective character to personal memories, they become the content of postmemory.